The Implementation of the Theory of Constraints (TOC) to Increase Production Cost Efficiency and Productivity: VAF Case Study - Vanomy, Afrianti Elsye; Engellika, Giovanny; Jeffrey, Jeffrey; Vanessa, Jolin; Liliana, Liliana; Te, Richardson; Zhang, Sherles; Stendy, Stendy; Vina, Vina; Viorensa, Viorensa (FIA UB, 2025)
VAF is a photo frame production company operating in the creative economy sector in Batam, Indonesia. VAF faced declining demand, leading to increased production costs and decreased productivity. After the post-pandemic drop in demand, VAF struggled with inefficiencies, rising costs, and labor constraints. This study applies the Theory of Constraints to diagnose production bottlenecks, quantify inefficiencies, and propose cost-saving strategies. In this quantitative descriptive study, the five steps of TOC and the application of Drum-Buffer-Rope and Buffer Management are implemented to enhance production cost efficiency and productivity. The analysis found that constraints stemmed from limited and unskilled labor, causing machines to operate suboptimally and delaying product delivery when demand fluctuated. Consequently, 84% of production time is allocated to value-added activities, while 16% is spent on non-value-added activities (material preparation and packing), which must be reduced to enhance operational efficiency. VAF achieved cost savings of 2.61% in 2022 and 2.19% in 2023 by minimizing non-value-added activities. Return on Investment in 2022 improved from -1.7% to -1.3%; in 2023, it rose from 3.3% to 4.1%. Total productivity increased by 2.80% in 2022 and 2.61% in 2023. Overall, TOC implementation successfully enhanced VAF’s production cost efficiency and productivity.